Systematic review of therapy used in relapsed or refractory diffuse large B-cell lymphoma and follicular lymphoma. (19th July 2018) - Galaznik, Aaron; Huelin, Rachel; Stokes, Michael; Guo, Yelan; Hoog, Meredith; Bhagnani, Tarun; Bell, Jill; Shou, Yaping
To identify real-world evidence on outcomes from therapies for relapsed/refractory diffuse large B-cell lymphoma (DLBCL) and follicular lymphoma (FL), we systematically reviewed literature in Medline/Embase for DLBCL/FL-related articles on real-world results published during January 2012–May 2016. Among 33 included articles, therapies included stem cell transplant (SCT) and chemotherapy, including experimental regimens. The highest overall survival rates were observed for SCT, long considered an optimal strategy following initial relapse. Prognoses were inferior among DLBCL patients receiving rituximab-based regimens rather than SCT, particularly among studies that exclusively focused on those ineligible for SCT due to age or co-morbidity. A lack of viable treatment options for DLBCL/FL patients ineligible for SCT after relapse remains a significant gap in care. Lay abstract: Non-Hodgkin lymphoma is the most prevalent blood cancer. Diffuse large B-cell lymphoma and follicular lymphoma account for nearly two-thirds of all non-Hodgkin lymphomas. One-third of patients with diffuse large B-cell lymphoma continue on to relapsed or refractory disease. While follicular lymphoma tends to be less aggressive, relapses do occur. Stem cell transplant and chemotherapy/immunotherapy are the current treatment options for relapsed or refractory patients. However, many patients are ineligible for stem cell transplant, due to age or preexisting medical conditions, so safe and effective treatment choices for these patients are a must. The lack of viable treatment options highlights this unmet need.